Comparative Effects of Backward Walk Training and Vestibular Therapy on Balance in Patients with Vestibular Disorders - Ayesha Malik, Anas Ali, Qurat Ul Ain, Mutahira Arslan, Unaiza Rehman, Ayesha Tabassam, Malik Muhammad Atif (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the effects of backward walking program and vestibular therapy on balance in patients with vestibular disorders. Method: A randomized clinical trial was conducted on 46 patients into 2 groups that were allocated randomly. Group A consisted of 23 participants and were asked for backward walk across the room, by asking the patient to backward walk on a slope and steps in upward and downward direction with open eyes for the duration of 30 minutes, 3 sessions per week for about 6 weeks along with routine physical therapy treatment which included postural training while 23 participants of Group B received vestibular therapy that included gaze stabilization exercises, and Brandt-Daroff exercises along with routine physical therapy which included postural and balance trainings for the duration of 6 weeks for 3 sessions/week for 30 minutes. Statistics scrutiny was done by SPSS software version 23. Results: Post treatment analysis indicated that a statistically significant difference was there in across the group comparison, and within the group comparison. An improvement was seen in the outcome measures of Berg Balance Scale that was statistically considerable within the group. Time for completing the task in Timed Up and Go Test also showed improvement within the groups (p< 0.05). The subjective estimation of the sign and symptoms evaluated with the usage of Visual Vertigo Analogue Scale showed a considerable improvement in each group. Practical Implication: Backward walk training was found to be beneficial in enhancing the balance amongst people with excessive hazard of fall whereas vestibular rehabilitation improved signs associated with vestibular disorders such as dizziness, lightheadedness, vertigo and imbalance. Conclusion: This study concluded that backward walk training and vestibular therapy were equally effective in dealing with vestibular related signs and symptoms and complications of the sufferers. Backward walk training was found to be beneficial in enhancing the balance amongst people with excessive hazard of fall whereas vestibular rehabilitation improved signs associated with vestibular disorders such as dizziness, lightheadedness, vertigo and imbalance. The results of this study helps the physiotherapist that they will add the vestibular therapy interventions and backward walk training for the patients having vestibular issue to reduce their balance issues and other symptoms such as dizziness , lightheadedness , gaze stabilization and vertigo for better results. Keywords: Balance, Backward walk training, Vestibular therapy, Gaze stabilization exercises, Cawthorne-Cooksey exercises.